Vertical plants: Plant design of Living walls – evaluation of 34 perennials in a textile based Living wall over a three years experiment - Stollberg, Maren; von Birgelen, Alexander (Frontiers in Horticulture, 2023)
The positive effects and importance of urban green infrastructure have been increasingly acknowledged recently. A possible way to increase vegetation in cities is vertical greening with living walls (LW). Knowledge of LW, including technique or their cooling effect, is well discussed, but little published data on plant diversity, design, and development in LWs exists. The plants themselves determine whether LWs achieve their intended benefits. However, LW plants are exposed to extreme conditions such as temperature or drought stress. Therefore, we observed plant development in a textile-based LW (mat) over a three-year experiment under a temperate oceanic climate. The aim was to establish higher plant diversity for use in LWs. We chose 34 perennials (shrubs, ferns, grasses, and geophytes) that require high soil moisture. The mat was soil-free and had to be overwatered with a nutrient solution. The perennials were grouped in the plant module “cascade” and “ground cover”. We created four experimental walls exposed to the south, north, west, and east and adapted the plant modules to the lighting conditions of the experiment wall. The modules were pre-cultivated and attached to the experimental walls in a randomised design and repetition of four. We determined the visual attractiveness and additional parameters of individual plants. We observed that Tellima grandiflora 'Rubra', Waldsteinia ternata, Pachysandra terminalis, and Heuchera Hybride 'Purple Petticoats' were the most attractive all year. Ajuga tenorii 'Mauro', Alchemilla caucasica, Hosta sieboldii 'Harry van Trier', Glechoma hederacea, and Geum coccineum 'Carlskaer' showed a nice ornamental effect and flowering during summer. The ferns and Waldsteinia ternata showed delayed growth but nice leaf texture gradually. We saw differences in winter survival rates depending on minimum temperature in winter. The tested plants developed a special vertical growth form and height. We observed various results at different expositions but found suitable species for each exposition. With these results, we derived a table of plants along with their suitability for LWs and determining conditions.